Efektivitas Pemanfaatan Sistem Informasi Pemerintah Daerah (SIPD) Dalam Penatausahaan Keuangan oleh Bendahara Pengeluaran pada Dinas Kependudukan dan Pencatatan Sipil Pemerintah Kota Sibolga - Roslianna Simatupang; Deliana; Meily Surianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to evaluate the Effectiveness of Utilizing the Local Government Information System (SIPD) in Financial Administration by the Expenditure Treasurer at the Population and Civil Registration Office of Sibolga City. SIPD is an important tool in financial management that aims to improve efficiency, transparency, and accountability in local government financial administration. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with the Expenditure Treasurer, the Head of the Finance Subdivision, and the SIPD Coordinator, as well as through direct observation and documentation. Data analysis was conducted using triangulation techniques to ensure data validity. The results showed that the effectiveness of SIPD utilization in the Population and Civil Registration Office of Sibolga City has provided various benefits, including increased speed and accuracy in financial data processing, ease of preparing financial reports, and increased compliance with financial regulations. However, some technical barriers are still faced, such as technical problems in the system and the need for further training for users such as the Expenditure Treasurer. From the perspective of the Technology Acceptance Model (TAM) theory, users showed a positive attitude towards SIPD with high perceived ease of use and usefulness, despite the need for increased technical support and training. The results of this study are expected to provide input for the development and improvement of SIPD utilization in financial administration in local governments, especially in Sibolga City.